The role of agricultural extension services on supporting circular bioeconomy in Indonesia - Yanfika, Helvi; Effendi, Irwan; Sumaryo,; Ansari, Andrianto (Frontiers in Sustainable Food Systems, 2024)
The global pursuit of sustainable development has highlighted the Circular Bioeconomy (CBE) as a key framework for resilience and sustainability. CBE, which focuses on regenerating natural resources and minimizing waste, encompasses sectors like agriculture, waste management, and renewable energy. Agricultural Extension Services (AES) play a pivotal role within this paradigm, serving as conduits for disseminating knowledge, providing training, and fostering innovation in the agricultural sector. Indonesia, with its rich agricultural heritage and diverse natural resources, stands as a key player in the global agricultural landscape. However, the country faces challenges such as land degradation, deforestation, and climate change impacts, necessitating a shift toward sustainable agricultural practices. This article examines the potential of CBE in Indonesia, particularly the role of AES in its adoption. AES bridge the gap between research, policy, and implementation, equipping farmers with the necessary tools and information for transitioning to CBE models. Despite challenges such as limited awareness, technological barriers, and policy constraints, strategic interventions and collaborative efforts can pave the way for effective CBE implementation in Indonesia. Strengthening collaboration, enhancing capacity-building efforts, advocating for supportive policies, mobilizing financial resources, and fostering public awareness are key strategies in this endeavor. In conclusion, successful CBE adoption in Indonesia depends on the active involvement of AES. Through embracing CBE principles and leveraging AES capabilities, Indonesia can achieve a sustainable and prosperous future, fostering resilience, economic growth, and environmental integrity.